2010
DOI: 10.1590/s0101-31222010000200017
|View full text |Cite
|
Sign up to set email alerts
|

Physical purity and germination of sugarcane seeds (caryopses) (Saccharum spp.)

Abstract: -Plant breeding is generally done through sexual reproduction even when the species is propagated asexually for commercial exploitation, as for example, in sugarcane. Therefore, the development of procedures to evaluate sugarcane seed viability is important for plant breeding programs. The objective of this research was to develop a methodology for analyzing the viability of sugarcane seeds (Saccharum spp.). Three crosses were used, two biparental crosses and one polycross. For the germination test study, two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 2 publications
1
3
0
2
Order By: Relevance
“…Based on these results, it shows that the percentage of sugarcane seed germination is low. This is in line with the results of research conducted by [3], [9], which stated that the germination of sugarcane seeds was low. In addition, [10] reported that the percentage of germination in sugarcane seeds from crosses was low and the maximum was only 49%.…”
Section: Viability and Vigor Of Sugarcane Seedssupporting
confidence: 92%
See 1 more Smart Citation
“…Based on these results, it shows that the percentage of sugarcane seed germination is low. This is in line with the results of research conducted by [3], [9], which stated that the germination of sugarcane seeds was low. In addition, [10] reported that the percentage of germination in sugarcane seeds from crosses was low and the maximum was only 49%.…”
Section: Viability and Vigor Of Sugarcane Seedssupporting
confidence: 92%
“…However, seed production from crosses is crucial for sugarcane genetic improvement programs. Genetic improvement was done by selecting the offspring population and cloning the superior offspring obtained from the crosses [3]. In sugarcane, the induction of flowering, crossing and seed production only occurs at a certain temperature and photoperiodicity.…”
Section: Introductionmentioning
confidence: 99%
“…Seed germination tests were conducted with three replicates of 100 spikelets per crossing. Spikelets were distributed on paper towel moistened with water equivalent to 2.5 times the paper weight, and then placed at bottom of plastic boxes (11.0 x 11.0 x 3.5 cm) under alternating temperature of 20-30 ºC and continuous light (Caieiro et al 2010). The number of normal seedlings was recorded daily to obtain index of germination rate (Maguire 1962).…”
Section: Seed Physiological Potentialmentioning
confidence: 99%
“…Comercialmente a cana-de-açúcar é multiplicada assexuadamente via propagação vegetativa, mesmo se tratando de reprodução sexuada (Caieiro et al, 2010). A propagação vegetativa da cana de açúcar ocorre a partir da germinação de cortes ou "gemas" presentes em seus colmos de até 1 m de comprimento, plantadas em sulcos (Netafim, 2013).…”
Section: Planta Da Cana-de-açúcarunclassified